2024
DOI: 10.1038/s41598-024-54804-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on the macro–micro evolution of compaction characteristics of coal gangue with different grain sizes under side-limit compression conditions

Zhenzhi Liu,
Ping Liu,
Zhen Lu
et al.

Abstract: Currently the main method of mine solid waste disposal and utilization is to apply gangue to underground filling. For the grading characteristics of coal gangue in the hollow zone in underground filling, the state of pressure and the mechanical properties of coal gangue filling materials under different particle sizes. In this paper, through laboratory tests and numerical simulations, the bearing characteristics and deformation damage of gangue are deeply investigated and analyzed from both macroscopic and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The research findings indicate that the stress of crushed gangue exhibits exponential growth with increasing strain, and there is a positive correlation between the compressive modulus and the compression rate. Liu et al 27 conducted laboratory experiments and numerical simulations to investigate the bearing characteristics and compression deformation patterns of gangue backfill materials with varying particle sizes. They found that as the particle size of gangue increases, the gangue particles are more susceptible to experiencing force chain instability and failure.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings indicate that the stress of crushed gangue exhibits exponential growth with increasing strain, and there is a positive correlation between the compressive modulus and the compression rate. Liu et al 27 conducted laboratory experiments and numerical simulations to investigate the bearing characteristics and compression deformation patterns of gangue backfill materials with varying particle sizes. They found that as the particle size of gangue increases, the gangue particles are more susceptible to experiencing force chain instability and failure.…”
Section: Introductionmentioning
confidence: 99%